ANALISIS DESKRIPTIF PROKRASTINASI AKADEMIK PADA MAHASISWA - Daniel Ade. K; Ka Rahman; Nur Hasanah Harahap (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Academic procrastination is a common issue among students, where they tend to delay assignments until approaching the deadline, which negatively affects academic performance and increases stress. This study aims to identify the factors influencing procrastination among Guidance and Counseling students at the University of Jambi. The research utilizes a quantitative method with a descriptive approach, involving 184 students as samples, selected through the total sampling method. Data were collected using a questionnaire consisting of 19 statements, with a reliability of 0.849 and an r table of 0.320. The data were analyzed using the C formula percentage to measure the level of academic procrastination. The results show that aspect 1, with 6 statement items, obtained the highest score in the 2021 cohort, aspect 2, with 7 statement items, had the highest score in the 2022 cohort, and aspect 3, with 6 statement items, also had the highest score in the 2022 cohort. Future studies are suggested to explore other aspects not covered by this research.